2014
DOI: 10.7227/ijmee.42.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Student Demographics and Outcomes in Mechanical Engineering in the U.S.

Abstract: Using a dataset from universities in the U.S. that includes over 90,000 first-time-in-college students and over 26,000 transfer students who majored in engineering, this work describes the demographics and outcomes for students starting in and transferring into Mechanical Engineering (ME). This aims to inform the decision making of faculty, department heads, and deans. Although men consistently outnumber women in ME, the rates of matriculation and six-year graduation vary by race/ ethnicity and gender. Retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 23 publications
(31 reference statements)
0
37
0
Order By: Relevance
“…Asian females typically have one of the highest graduation rates in engineering [41,54,55], but in ASE, their graduation rate is the third lowest of the race/ethnicity-gender groups (an alarming difference of 22 percentage points). As shown in [43], all race/ethnicitygender groups have higher graduation rates in mechanical engineering than in ASE, except Hispanic females. Among Asian females, ASE lags mechanical engineering by more than 10 percentage points.…”
Section: B Who Succeeds In Ase?mentioning
confidence: 87%
See 2 more Smart Citations
“…Asian females typically have one of the highest graduation rates in engineering [41,54,55], but in ASE, their graduation rate is the third lowest of the race/ethnicity-gender groups (an alarming difference of 22 percentage points). As shown in [43], all race/ethnicitygender groups have higher graduation rates in mechanical engineering than in ASE, except Hispanic females. Among Asian females, ASE lags mechanical engineering by more than 10 percentage points.…”
Section: B Who Succeeds In Ase?mentioning
confidence: 87%
“…One of the few studies that disaggregated by gender and discipline found that women were more likely to persist in mechanical engineering (ME) than their male counterparts; however, ASE was not offered at that institution [41]. Prior research in ME asserts that "women outpersist men in ME, and Hispanic students are more likely to leave ME than other engineering majors" [42]. ME and ASE curricula often have significant overlap, which could lead to similar trends in enrollment and student outcomes, but that is not always the case [43].…”
Section: Previous Studies Of Aerospace Engineering Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings give weight to the need for understanding not only what experiences impact students' choice of engineering in general, but also their choice of specific engineering disciplines. Nevertheless, the data in these studies are limited to high school transcripts which include standardized scores and course taking, but not out-of-school experiences (Lord, Ohland, Layton, & Orr, 2013;Orr, Lord, Layton, & Ohland, 2014). Our work examines specifically how informal STEM experiences in high school influence differential choices with specific engineering disciplines that students choose in college.…”
Section: Introductionmentioning
confidence: 99%
“…(Lord, Layton, & Ohland, 2014, page 4) Additional research has also employed the stickiness measure as a metric of student success. For example, research on longitudinal success rates in Civil and Mechanical Engineering students has used stickiness as a metric to gauge the differences between genders and ethnicities in these fields (Ohland, Lord, & Layton, 2015;Orr, Lord, Layton, & Ohland, 2014). The present study will apply the metric of stickiness to NTS to show trends within this population of students.…”
Section: Stickiness As a Metric Of Successmentioning
confidence: 99%